EXPERTS WORKSHOP ON THE STUDY AND CONSERVATION OF EARTHEN ARCHITECTURE IN THE MEDITERRANEAN REGION - Achenza, Maddalena; Cancino, Claudia; Correia, Mariana; Ferron, Amila; Guillaud, Hubert (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
The study and conservation of earthen architecture has developed significantly throughout the last two decades in the Mediterranean region. To initiate greater cooperation among Mediterranean countries, a group of professionals with expertise in the subject from eleven representative countries convened for a series of structured discussions - within the framework of an Experts Workshop - on the challenges facing the field. The ultimate objective of the workshop, which occurred in March of 2009 on Sardinia in Italy, was to develop an action plan for coordinating the advancement of the discipline within the Mediterranean region. The participants identified training and research needs, priorities, available resources, and potential strategies for two themes: the conservation and management of earthen sites and earthen architecture for sustainable development. The recent development of the study and conservation of earthen architecture in the Mediterranean region has been accomplished through a series of international conferences, training initiatives, formation of national and international committees and the resulting network of practitioners, scientists and academics. Seeking to facilitate the development the field within the Mediterranean region, Project TERRA - a collaborative initiative of the School of Architecture of Grenoble (CRATerre-EAG), the Getty Conservation Institute (GCI), and the International Centre for the Study of the Preservation and the Restoration of Cultural Property (ICCROM) - initiated the TERRAMed project in 2004 to collect and analyze information on past and present activities in Mediterranean countries. In 2005, the Diparch- Universitá di Cagliari (UNICA), the Escola Superior Gallaecia (ESGallaecia) and CRATerre-École Nationale Supérieure d’Architecture de Grenoble (CRATerre-ENSAG) organized the first Mediterranean Conference on Earthen Architecture (MEDITERRA 2009). GCI joined the group to co-organize an experts workshop as part of the MEDITERRA 2009 general program. This paper presents the planning process, identified objectives, action plan development methodology, and general discussion of results from the Experts Workshop.